INVESTMENT ATTRACTIVENESS OF GREEN PROJECTS: ESG ASPECTS - Maltseva, Yuliana; Maksymets, Olena (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The paper examines the peculiarities of shaping the investment attractiveness of green projects in the context of the transformation of the modern economy and the growing importance of non-financial factors. The significance of the ESG approach (Environmental, Social, Governance) as a key tool for assessing the long-term sustainability of enterprises is substantiated. The specifics of implementing ESG principles in the agricultural sector are revealed, and the main barriers and risks, including technological, financial, regulatory, and market-related ones, are identified. Global trends in the development of green investments and their impact on economic growth and environmental transformation are analyzed. The study proves the necessity of integrating ESG criteria into the system for assessing the investment attractiveness of enterprises in order to enhance their competitiveness, transparency, and access to international financing.